Cryopreserved Placental Derivatives Improve Quality of Life and Behavioral Responses in Mice with Chemotherapy-Induced Ovarian Failure - Shevchenko Mariіa; Mykhalchuk, Tetyana; Prokopіuk Olga; Karpenko, Volodymyr; Prokopіuk Volodymyr (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4): 274–279